To the moon and back : a novel - Kingsbury, Karen (Kingsbury, Karen. Baxter family, 2018)
Brady Bradshaw was a child when the Oklahoma City bombing took his mother from him. Every year, Brady visits the site on the anniversary to remember her. A decade ago on that day, he met Jenna Phillips, who was also a child when her parents were killed in the attack. Brady and Jenna shared a deep heart connection and a single beautiful day together at the memorial. But after that, Brady never saw Jenna again. Every year when he returns, he leaves a note for her in hopes that he might find her again. This year, Ashley Baxter Blake and her sister Kari Ryan take a spring break trip with their families that includes a visit to the site to see the memorial's famous Survivor Tree. While there, Ashley spots a young man, alone and troubled. A chance moment leads Ashley to help the young man find the girl he can't forget--Jenna Phillips. Ashley's family is skeptical, but in the end everyone comes together to support Ashley's efforts to find the girl and bring them together. But will it work? And is a shared heartache enough reason to fall in love? Deeply emotional and beautifully romantic, To the Moon and Back is an unlikely love story about healing, redemption, and hope that springs from the ashes of a tragedy.